The Supreme Court, Endrew, and the Appropriate Education of Students With Disabilities. (January 2018) - Turnbull, H. Rutherford; Turnbull, Ann P.; Cooper, David H.
In this article, we analyze the Supreme Court's decision in Endrew F. v. Douglas County School District RE-1 (2017), interpreting the Individuals with Disabilities Education Act (IDEA) and its provisions creating a right of every student with a disability to have an appropriate education. We compare the Endrew decision with IDEA and the Court's previous appropriate education decision, Board of Education of the Hendrick Hudson Central School District v. Rowley (1982), on four key concepts: educational program, reasonably calculated, progress, and child's circumstances. We discuss the case's implications for systems capacity development and interpret Endrew as a narrative about students' ethical claim to dignity.